Deskripsi Penanaman Nilai-Nilai Moderasi Beragama pada Anak Usia Dini di TK Al-Ishlah - Leidi Mohi; Nurhayati Tine; Sulastya Ningsih (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Religious moderation in early childhood is an effort to instill moderate religious values in children from a young age. These values include tolerance, fairness, balance, and equality. One of the primary methods used to cultivate these values is the habit-formation method. This study aims to describe how religious moderation values are introduced and developed in early childhood at Al-Ishlah Kindergarten. The research question explored is: How are the values of religious moderation instilled in early childhood at TK Al-Ishlah? This study employed a descriptive qualitative approach. Data were collected through interviews and documentation and analyzed using qualitative descriptive methods. The results show that the forms of religious moderation taught at TK Al-Ishlah include practices such as performing ablution, prayer practice, repeating and memorizing short surahs and daily prayers, and introducing places of worship from various religions. In addition, the learning process incorporates values such as honesty, politeness, cooperation, and mutual respect. The steps taken in implementing religious moderation values at Al-Ishlah Kindergarten include the teacher acting as a role model, lesson planning, parental involvement, and organizing religious activities.